The Aisyiyah Women's Preaching Movement in Assisting Divorce Cases - Fitri Sukma Wati; Santa Rusmalita; Patmawati Patmawati (State Institute of Islamic Studies Batusangkar, 2023)
The family is the smallest part of society. Whole and harmonious family is coveted by every family. But not all couples can maintain a harmonious family. There are many families who have problems in their households so that they file for divorce at the Religious Courts. the divorce rate is also high. The ‘Aisyiyah women's organization feels compelled to provide divorce assistance. ‘Aisyiyah, who oversees the Law and Human Rights Council, formed a Legal Aid Post (posbakum) which is engaged in providing assistance in divorce cases. The method used is a qualitative approach with descriptive methods. The results of the research are that the Posbakum carry out mediation, using several approaches, namely the faith approach, the worship approach and the psychological approach. The results of the mediation can be seen through the data, namely out of 15 cases handled during a year, 7 cases canceled their divorce plans and 8 cases continued. Obstacles encountered in mediation are internal and external. From the internal partner, there is an ego that is still put forward by each partner. There are also those who are infected with disease. Meanwhile, externally there is family intervention, so that the couple continues their separation.